Metformin as a Potential Neuroprotective Agent in Prodromal Parkinson's Disease—Viewpoint - Sportelli, Carolina; Urso, Daniele; Jenner, Peter; Chaudhuri, K. Ray (Frontiers in Neurology, 2020)
To date, there are no clinically effective neuroprotective or disease-modifying treatments that can halt Parkinson’s disease (PD) progression. The current clinical approach focuses on symptomatic management. This failure may relate to the complex neurobiology underpinning the development of PD and the absence of true translational animal models. In addition, clinical diagnosis of PD relies on presentation of motor symptoms which occur when the neuropathology is already established. These multiple factors could contribute to the unsuccessful development of neuroprotective treatments for PD. Prodromal symptoms develop years prior to formal diagnosis and may provide an excellent tool for early diagnosis and better trial design. Patients with idiopathic rapid eye movement behaviour disorder (iRBD) have the highest risk of developing PD and could represent an excellent group to include in neuroprotective trials for PD. In addition, repurposing drugs with excellent safety profiles is an appealing strategy to accelerate drug discovery. The anti-diabetic drug metformin has been shown to target diverse cellular pathways implicated in PD progression. Multiple studies have, additionally, observed the benefits of metformin to counteract other age-related diseases. The purpose of this viewpoint is to discuss metformin’s neuroprotective potential by outlining relevant mechanisms of action and the selection of iRBD patients for future clinical trials in PD.